Repurposing p97 inhibitors for chemical modulation of the bacterial ClpB–DnaK bichaperone system - Glaza, Przemyslaw; Ranaweera, Chathurange B.; Shiva, Sunitha; Roy, Anuradha; Geisbrecht, Brian V.; Schoenen, Frank J.; Zolkiewski, Michal (My University, 2021)
The ClpB–DnaK bichaperone system reactivates aggregated cellular proteins and is essential for survival of bacteria, fungi, protozoa, and plants under stress. AAA+ ATPase ClpB is a promising target for the development of antimicrobials because a loss of its activity is detrimental for survival of many pathogens and no apparent ClpB orthologs are found in metazoans. We investigated ClpB activity in the presence of several compounds that were previously described as inhibitor leads for the human AAA+ ATPase p97, an antitumor target. We discovered that N2,N4-dibenzylquinazoline-2,4-diamine (DBeQ), the least potent among the tested p97 inhibitors, binds to ClpB with a Kd∼60 μM and inhibits the casein-activated, but not the basal, ATPase activity of ClpB with an IC50∼5 μM. The remaining p97 ligands, which displayed a higher affinity toward p97, did not affect the ClpB ATPase. DBeQ also interacted with DnaK with a Kd∼100 μM and did not affect the DnaK ATPase but inhibited the DnaK chaperone activity in vitro. DBeQ inhibited the reactivation of aggregated proteins by the ClpB–DnaK bichaperone system in vitro with an IC50∼5 μM and suppressed the growth of cultured Escherichia coli. The DBeQ-induced loss of E. coli proliferation was exacerbated by heat shock but was nearly eliminated in a ClpB-deficient E. coli strain, which demonstrates a significant selectivity of DBeQ toward ClpB in cells. Our results provide chemical validation of ClpB as a target for developing novel antimicrobials. We identified DBeQ as a promising lead compound for structural optimization aimed at selective targeting of ClpB and/or DnaK.
Keywords: AAA+ ATPase; Antimicrobial compound; ClpB; DnaK; molecular chaperone; Protein aggregation